1994
DOI: 10.1016/0014-5793(94)00755-1
|View full text |Cite
|
Sign up to set email alerts
|

Iron deprivation‐induced apoptosis in HL‐60 cells

Abstract: Iron deprivation of HL-60 cells with deferoxamine B mesylate (DFO) induced apoptosis. DNA fragmentation became apparent with 10Wh M DFO after 48 h treatment. The apoptosis peak according to the DNA histogram on flow cytometory and typical nuclear collapse and were observed microscopically after 48 h treatment with low4 M DFO. Cells treated with 10e4 M DFO for as little as 24 h were shown to be committed to apoptosis, as chromatin condensation progressed gradually thereafter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 6 publications
4
53
1
Order By: Relevance
“…Although it has been shown that DFB has a toxic effect on eukaryotic cells (Fukuchi et al 1994, Leardi et al 1998, we have demonstrated that this is not the case for our heterotrophic bioreporter (Fig. 5).…”
Section: Specificity Of Fe-siderophore Acquisition and Cross-utilizationcontrasting
confidence: 72%
“…Although it has been shown that DFB has a toxic effect on eukaryotic cells (Fukuchi et al 1994, Leardi et al 1998, we have demonstrated that this is not the case for our heterotrophic bioreporter (Fig. 5).…”
Section: Specificity Of Fe-siderophore Acquisition and Cross-utilizationcontrasting
confidence: 72%
“…For example, iron chelation has been demonstrated to induce apoptosis (Fukuchi et al, 1994;Haq et al, 1995) and promote cell-cycle arrest (Lederman et al, 1984). Similarly, cellular hypoxia represents a potent stimulus for the apoptotic cascade (for a review, see Brunelle and Chandel, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…DFO, that mimics hypoxia and a similar oxygen sensor in the hypoxia regulation, induces a hypoxic condition (Tazuke et al, 1998;Park et al, 2000;Park et al, 2001a). The effect of DFO on DNA synthesis and repair was reflected in studies that have shown that treatment with DFO induces apoptosis in rapidly growing tumor cells (Fukuchi et al, 1994;Simonart et al, 2000). This new finding indicates that there is another pathway that is different from the HIF-1 signaling pathway, which is known as a major mechanism in hypoxia signaling.…”
Section: Introductionmentioning
confidence: 96%